Stability of thin-shell wormholes supported by normal matter in Einstein-Maxwell-Gauss-Bonnet gravity - Mazharimousavi, S. Habib; Halilsoy, M.; Amirabi, Z. (Amer Physical Soc, 2010)
Recently in [Phys. Rev. D 76, 087502 (2007) and Phys. Rev. D 77, 089903 (2008)] a thin-shell wormhole has been introduced in five-dimensional Einstein-Maxwell-Gauss-Bonnet gravity which was supported by normal matter. We wish to consider this solution and investigate its stability. Our analysis shows that for the Gauss-Bonnet parameter alpha < 0, stability regions form for a narrow band of finely tuned mass and charge. For the case alpha > 0, we iterate once more that no stable, normal matter thin-shell wormhole exists.